A novel N95 respirator with chitosan nanoparticles: mechanical, antiviral, microbiological and cytotoxicity evaluations - Marcela Guimarães Landim; Marcella Lemos Brettas Carneiro; Graziella Anselmo Joanitti; Carla Tatiana Mota Anflor; David Dobkowski Marinho; José Filipe Bacalhau Rodrigues; Wladymyr Jefferson Bacalhau de Sousa; Daniel de Oliveira Fernandes; Beatriz Ferreira Souza; Alicia Simalie Ombredane; Jessica Catarine Frutuoso do Nascimento; Gisela de Jesus Felice; et al. (Discover Nano, 2023)
Abstract Background It is known that some sectors of hospitals have high bacteria and virus loads that can remain as aerosols in the air and represent a significant health threat for patients and mainly professionals that work in the place daily. Therefore, the need for a respirator able to improve the filtration barrier of N95 masks and even inactivating airborne virus and bacteria becomes apparent. Such a fact motivated the creation of a new N95 respirator which employs chitosan nanoparticles on its intermediate layer (SN95 + CNP). Results The average chitosan nanoparticle size obtained was 165.20 ± 35.00 nm, with a polydispersity index of 0.36 ± 0.03 and a zeta potential of 47.50 ± 1.70 mV. Mechanical tests demonstrate that the SN95 + CNP respirator is more resistant and meets the safety requisites of aerosol penetration, resistance to breath and flammability, presenting higher potential to filtrate microbial and viral particles when compared to conventional SN95 respirators. Furthermore, biological in vitro tests on bacteria, fungi and mammalian cell lines (HaCat, Vero E6 and CCL-81) corroborate the hypothesis that our SN95 + CNP respirator presents strong antimicrobial activity and is safe for human use. There was a reduction of 96.83% of the alphacoronavirus virus and 99% of H1N1 virus and MHV-3 betacoronavirus after 120 min of contact compared to the conventional respirator (SN95), demonstrating that SN95 + CNP have a relevant potential as personal protection equipment. Conclusions Due to chitosan nanotechnology, our novel N95 respirator presents improved mechanical, antimicrobial and antiviral characteristics.